Exercise types for reading comprehension in foreign language classes (Educational Dimension, 2020)
The paper deals with the problem of selecting the types of reading comprehension exercises in a foreign language lesson. It identifies the role of reading as a receptive skill and one of the main competences in learning a foreign language. Distinctive differences between an exercise and a task as didactic forms of teaching and their importance in the formation of speech competences have been established. Modern approaches to the typology of exercises have been analyzed depending on the learning goals and receptive or productive types of speaking activity. The main types of exercises aimed at developing communicative language competences include receptive, reproductive, reproductive-productive, productive, closed- and open-type exercises, content- and form-oriented exercises. The scientific paper argues that textual competence is a component of language competence in modern didactics, and reading is defined not only as a receptive process, but also as an interactive and constructive process, since the information obtained from the text is related to one’s own knowledge and experience, on the basis of which new knowledge is acquired. It is also emphasized that the process of working with a text consists of three main stages: pre-text, text, and post-text stages, each providing the corresponding types of exercises or tasks. The main types of text exercises include: gap filling, substitution, error correction exercises, reproductive exercises, productive exercises, questioning, test exercises, structure exercises, exercises for overcoming language difficulties, exercises involving the native language, and non-verbal exercises. Gap-filling exercises are designed to check text comprehension. Substitution exercises are divided into formal, content, general comprehension of the text format, general comprehension of the text content, and detailed comprehension exercises. Error correction exercises make it possible to better learn semantic and grammatical material of the text. Reproductive exercises include listening to the text while reading it, as well as text reconstruction. Productive exercises provide answers to questions about the content of the text. Questioning exercises are divided into content-dependent and content-free exercises that are suitable for any text. Typical test exercises are multiple-choice questions, true/false statements and gap filling. Structure exercises include dividing the text into paragraphs, arranging the events in the correct order, etc. Exercises for overcoming language difficulties include defining the type of text, vocabulary exercises, grammatical structures exercises, and activating prior knowledge. Non-verbal exercises are based on schematic representation of the content in the form of diagrams, tables, etc.